2020
DOI: 10.3389/fcell.2020.576482
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal Dysfunction Contributes to White Matter Injury Following Subarachnoid Hemorrhage in Rats via Thioredoxin-Interacting Protein-Dependent Manner

Abstract: Background and Purpose: White matter injury (WMI) exists in the early stage of subarachnoid hemorrhage (SAH) and has not been well addressed so far. Methods: We utilized short hairpin RNA (shRNA) and clustered regularly interspaced short palindromic repeats (CRISPR) to verify the role of peroxisomes in WMI following SAH. We evaluated short-and long-term neurobehavior after SAH. Western blotting, immunofluorescence, and Golgi staining techniques were performed to assess the changes in protein levels. Results: C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Furthermore, the white matter injury occurring at the early stage of SAH has not been addressed well so far. Recently, the damage caused by the SAH peroxisome in mouse models was found to escalate white matter injury to SAH, and was partially mediated by TXNIP and glycerone-phosphate acyl-transferase pathways [ 107 ].…”
Section: The Role Of Txnip In Diseasesmentioning
confidence: 99%
“…Furthermore, the white matter injury occurring at the early stage of SAH has not been addressed well so far. Recently, the damage caused by the SAH peroxisome in mouse models was found to escalate white matter injury to SAH, and was partially mediated by TXNIP and glycerone-phosphate acyl-transferase pathways [ 107 ].…”
Section: The Role Of Txnip In Diseasesmentioning
confidence: 99%
“…TNFα, IL-1β, IL-6 and other molecules can directly affect the structure and function of the myelin sheath (Simard et al, 2012;Egashira et al, 2015;Xu et al, 2020). Moreover, ROS are involved in the TXNIP and GNPAT signaling pathways (Xu et al, 2020).…”
Section: Involved Brain Cellsmentioning
confidence: 99%
“…The downregulation of par1 expression with par1 siRNA can promote myelin regeneration after SAH (6). Recent studies have also found that after SAH, the administration of catalase CRISPR (clustered regularly interspaced short palindromic repeats) to rats can also prominently increase the expression of myelin basic protein (MBP), while also reducing APP, IL-6 and TNF α and subsequently cricially alleviate the neurological deficit (Xu et al, 2020). Generally, to treat myelin sheath injury after SAH, previous researchers have conducted many informative explorations from different aspects and obtained many important achievements, which have provided experimental conclusions and research experience for future precise treatments.…”
Section: Treatment Strategy For Myelin Sheath Injury Caused By Sahmentioning
confidence: 99%
“…supply during the myelination process, which requires a high oxygen consumption. Xu and colleagues recently reported that perioxisomal dysfunction exacerbated white matter injury after SAH, at least partly through thioredoxin-interacting protein and glycerone phosphate acyl transferase signals (84).…”
Section: Repair Factors Of White Matter After Sah Oligodendrocyte Precursor Cellsmentioning
confidence: 99%